Studi Literatur Upaya Meningkatkan Keterampilan Passing Dalam Permainan Bola Basket Dengan Berbagai Macam Metode Pembelajaran - Dian Imam Saefulah; Kusmiyati Kusmiyati; Hasan Tholabi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
This research is motivated by the large number of learning models used in an effort to improve passing skills in basketball games so that the learning methods used to improve passing skills are less than optimal. The aim of this research is to find out suitable learning methods to use in improving passing skills in the game of basketball. The method used in this research is library research, with the collection method used is documentation. In completing this research, the data used is secondary data, namely data originating from sources in the form of books, journals and articles that are appropriate to this research. There are sixteen journals used by researchers as sources for this research. These results prove that there are a variety of learning methods that can be used when learning passing in the game of basketball. Therefore, researchers group them according to the methods used, such as variation game methods, passing exercises, scientific learning and cooperative learning.